Pengaruh Pendapatan Asli Daerah, Dana Alokasi Umum, dan Dana Alokasi Khusus terhadap Belanja Daerah Kabupaten/Kota Pada Provinsi Jawa Barat dan Banten - Yenada, Kefas Bernadinova; Muslimin, Muslimin (Reslaj : Religion Education Social Laa Roiba Journal, 2024)
To attain autonomy at the regional level, local administrations must efficiently and effectively manage available resources. The decentralization strategy, which granted greater authority to the states, made this feasible. Examining how PAD, GAF, and SAF affect local budgets in West Java and Banten is the primary objective of this research. The Regional Revenue and Expenditure Budget Realization Report for the Provinces of West Java and Banten covers the years 2017-2021 and provides numerical analysis of regional own revenues, general allocation funds, special allocation funds, and regional expenditures. Statistics and hypothesis testing in SPSS 24. Data for hypothesis testing was analyzed using multiple linear regression. The research indicated that (1) the PAD correlates positively with the Regional Expenditure of Regency/City Governments in West Java and Banten, and the greater the PAD, the higher the Regional Expenditure. Since the General Allocation Fund is positively correlated with Regional Expenditures, raising the GAF would likewise raise the Regional Expenditures of District/City Governments in West Java and Banten. Similarly, rising DAK will boost spending by Java Island's regional district and city governments. Keywords: Regional Original Income, General Allocation Fund, Special Allocation Fund, Regional Expenditure.